Diagnostic and surgical management of patients with aneurysms of the thoracic aorta with various causes. Echocardiography and contrast enhanced computed tomography in prophylactic replacement of the ascending aorta. Issue 1 (January 1986) - Bruno, L; Prandi, M; Colombi, P; La Vecchia, L
Abstract : Sixty eight patients with aneurysms of the thoracic aorta were studied. Forty one had aortic dissection, 24 had dilatation only, and three had transverse aortic rupture. Sixteen had Marfan's syndrome; 17 had hypertension; and in eight there were other causal factors. In 17 the cause of the aneurysm was unknown. Histological examination did not help to establish the cause of aneurysm. Echocardiography failed to detect dissection of the ascending aorta in four (21%) out of 19 cases studied. The mortality rate in the whole series was 26%. Early (operative and hospital) and late deaths occurred in 20% and 6% of patients respectively. The early mortality rate was 40% in the 24 emergency cases of dissection of the ascending aorta, 9% in patients operated on for dilatation of the ascending and transverse aorta without dissection, and 8% in patients with chronic dissection of the ascending aorta who had elective operation. Early and late mortality rates were no higher in patients with Marfan's disease than in any of the other groups. It is suggested that contrast enhanced computer tomography should be performed in all patients with pronounced aortic root dilatation and in patients with Marfan's disease with symptoms which suggest dissection, even if they have only slight aortic root dilatation. Preventive replacement of the ascending aorta should be considered in more patients to reduce the number of emergency operations, in which the mortality rate is high. There is no definite limit of aortic root dilatation above which preventive replacement of the ascending aorta should be routinely considered.